The Effect Of Process-Oriented Guided-Inquiry Learning On Students’ Scientific Inquiry Literacy Skills And Achievement In Secondary School Chemistry - Abdul Talib, Corrienna (2013)
The quality of education that teachers provide to students is highly dependent upon what teachers do in the classroom. In preparing students of today to become successful individuals of tomorrow, chemistry teachers need to ensure that their teaching is effective. Teachers should have the knowledge of how students learn and how best to teach chemistry. Changing the way teachers teach and what to teach in chemistry is a continuing professional concern. Efforts should be taken now to direct the presentation of chemistry lessons away from the conventional methods to a more student centered approach. In the study, a student-centered learning style was introduced as an alternative approach to teaching in Malaysian schools. The paper aimed to examine the relative impacts of Process-Oriented Guided-Inquiry Learning (POGIL) on students’ scientific literacy skills and achievement in chemistry specifically under the topic of Acids and Bases. POGIL is a technique-focused and uses guided-inquiry activities to develop understanding. Research studies reveal that the campus where the environment is fascinating for students and they feel ease and enjoyment, their achievement is good.